2015
DOI: 10.1093/ejcts/ezv397
|View full text |Cite
|
Sign up to set email alerts
|

Impact of levosimendan and ischaemia–reperfusion injury on myocardial subsarcolemmal mitochondrial respiratory chain, mitochondrial membrane potential, Ca2+cycling and ATP synthesis

Abstract: LS limited RCF at complex IV and V with ΔΨm hypopolarization suggesting a specific [Formula: see text]-dependent pathway. Ca(2+) redistribution from SSM by LS during I/R injury possibly prevents from Ca(2+) overload due to mPTP flickering. LS-induced mPTP flickering did not promote permanent Ca(2+)-induced mPTP opening. LS-dependent inhibition of ATP generation presumably resulted from complex IV and V limitations and lowered ΔΨm. However, a resulting impact of limited ATP synthesis on myocardial recovery rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…ATP is essential for maintaining Δψm (Xu et al, 2001; Krayl et al, 2007). Recently, Sommer et al (2016) reported that low Δψm could depress ATP synthesis and transportation. Consistent with this, our data found that Δψm declining followed by impairment of mitochondrial ATP synthesis in shPOLG-treated cells, implying Δψm is a sensitive indicator for mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…ATP is essential for maintaining Δψm (Xu et al, 2001; Krayl et al, 2007). Recently, Sommer et al (2016) reported that low Δψm could depress ATP synthesis and transportation. Consistent with this, our data found that Δψm declining followed by impairment of mitochondrial ATP synthesis in shPOLG-treated cells, implying Δψm is a sensitive indicator for mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these pharmacological actions, levosimendan improves atrio-ventricular coupling and cardiac mechanical efficiency without increasing myocardial oxygen consumption [10][11][12][13]. Moreover, levosimendan has been shown to have a direct effect on mitochondria [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although myocardial reperfusion therapy is essential, reperfusion itself can induce myocardial damage and increase infarct size due to an increase in reactive oxygen species (ROS) production in the ischemic myocardium . It is known that cardiac mitochondria are involved in the heart, including ATP synthesis, energy metabolism, apoptotic regulation as well as Ca 2+ homeostasis . Studies reported that these events were disturbed and lead to myocardial damage during myocardial ischemia/reperfusion (I/R) injury .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that cardiac mitochondria are involved in the heart, including ATP synthesis, energy metabolism, apoptotic regulation as well as Ca 2+ homeostasis . Studies reported that these events were disturbed and lead to myocardial damage during myocardial ischemia/reperfusion (I/R) injury . In addition, I/R injury can markedly increase ROS levels in cardiomyocytes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation